2000
DOI: 10.1177/00220345000790011401
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of MMP-8 in Human Odontoblasts and Dental Pulp Cells is Down-regulated by TGF-β1

Abstract: Recent findings show that matrix metalloproteinase-8 (MMP-8) is expressed, in addition to neutrophils, by human chondrocytes, cultured fibroblasts, and endothelial cells. We investigated the expression of MMP-8 in other human mesenchyme-derived cells, odontoblasts, and pulp tissue. Odontoblasts and pulp tissue were collected from extracted human teeth for MMP-8 mRNA analysis with reverse-transcription/polymerase chain-reaction (RT-PCR) and Southern blot. The expression, localization, and secretion of MMP-8 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0
13

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 43 publications
6
131
0
13
Order By: Relevance
“…High levels of neutrophils and accompanying MMP-8 also correlate with the fibrotic state in patients suffering from hypersensitivity pneumonitis . Other groups have shown that MMP-8 is down-regulated during the course of lung fibrosis (Ruiz et al, 2003), which could be attributed to increased levels of TGF-b, being associated to a decrease of MMP-8 expression (Moilanen et al, 2002;Palosaari et al, 2000). These data indicate that a shift from highly regulated MMP-8 expression to exaggerated, mainly PMN-driven, MMP-8 release might trigger the pathogenesis of fibrosis by disturbing the delicate balance that exists in matrix turnover.…”
Section: Neoplastic Diseasesmentioning
confidence: 88%
“…High levels of neutrophils and accompanying MMP-8 also correlate with the fibrotic state in patients suffering from hypersensitivity pneumonitis . Other groups have shown that MMP-8 is down-regulated during the course of lung fibrosis (Ruiz et al, 2003), which could be attributed to increased levels of TGF-b, being associated to a decrease of MMP-8 expression (Moilanen et al, 2002;Palosaari et al, 2000). These data indicate that a shift from highly regulated MMP-8 expression to exaggerated, mainly PMN-driven, MMP-8 release might trigger the pathogenesis of fibrosis by disturbing the delicate balance that exists in matrix turnover.…”
Section: Neoplastic Diseasesmentioning
confidence: 88%
“…We observed reduced MMP-8 levels in obese women, which may be explained by the negative regulation of MMP-8 expression by biomolecules such as transforming growth factor-beta 1 (TGF-β1) that are elevated in obesity [28] and that strongly downregulate MMP-8 [29], while stimulating MMP-9 expression [30]. To exclude the possibility of decreased MMP-8 levels due to reduced neutrophil activation, we measured the plasma MPO activity.…”
Section: Discussionmentioning
confidence: 99%
“…The odontoblasts in developed human teeth synthesize and release several MMPs, including collagenase-2 (MMP-8) (Palosaari et al, 2000), gelatinases (MMP-2 and -9) (Tjäderhane et al, 1998b), membrane-bound MMP-14 (MT1-MMP) (Palosaari et al, 2002), enamelysin (MMP-20) (Sulkala et al, 2002) and cathepsin D (Linde and Persliden, 1977). The latent and active forms of gelatinolytic species (e.g.…”
Section: Structure Property and Function Of Mmps In Dentinmentioning
confidence: 99%